2000
DOI: 10.1074/jbc.m001291200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Nucleotide Incorporation by Mammalian DNA Polymerase δ

Abstract: The kinetics of nucleotide incorporation into 24/36-mer primer/template DNA by purified fetal calf thymus DNA polymerase (pol) ␦ was examined using steadystate and pre-steady-state kinetics. The role of the pol ␦ accessory protein, proliferating cell nuclear antigen (PCNA), on DNA replication by pol ␦ was also examined by kinetic analysis. The steady-state parameter k cat was similar for pol ␦ in the presence and absence of PCNA (0.36 and 0.30 min ؊1 , respectively); however, the K m for dNTP was 20-fold highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 41 publications
9
81
1
Order By: Relevance
“…One possibility is that PCNA that is loaded onto DNA may increase the processivity of UNG2 by decreasing the dissociation of the enzyme from DNA. Einolf and Guengerich [50] found that the K d of calf thymus DNA polymerase δ for DNA increased five-fold in the absence of PCNA. The authors concluded that PCNA appeared to affect Pol δ replication mainly by decreasing the dissociation of the polymerase from DNA [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that PCNA that is loaded onto DNA may increase the processivity of UNG2 by decreasing the dissociation of the enzyme from DNA. Einolf and Guengerich [50] found that the K d of calf thymus DNA polymerase δ for DNA increased five-fold in the absence of PCNA. The authors concluded that PCNA appeared to affect Pol δ replication mainly by decreasing the dissociation of the polymerase from DNA [50].…”
Section: Discussionmentioning
confidence: 99%
“…Einolf and Guengerich [50] found that the K d of calf thymus DNA polymerase δ for DNA increased five-fold in the absence of PCNA. The authors concluded that PCNA appeared to affect Pol δ replication mainly by decreasing the dissociation of the polymerase from DNA [50]. A second possibility is that the UNG2·PCNA interaction serves to increase the affinity of UNG2 for (non-uracil-containing) DNA, which is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme extending SP and S 0 P 0 to form D (Table I) is assumed to be fully processive that does not dissociate after the addition of each nucleotide. Most DNA polymerase enzymes are processive where once bound, they can add more than 200 nucleotides before dissociating (Einolf and Guengerich, 2000;Lowe and Guengerich, 1996). In addition, for the short templates typical of quantitative PCR, the nucleotide incorporation error rate is expected to be negligible.…”
Section: Extensionmentioning
confidence: 99%
“…However, the extent to which the mammalian forms are able to copy past chemical lesions other than photodamaged pyrimidines is largely unexplored, and the question of how lesions interact with replicative DNA polymerases is important. Recently we used purified calf thymus DNA pol ␦, considered to be the main leading strand DNA polymerase (1,2), in a series of steady-state and pre-steadystate kinetic experiments and concluded that the major features of the catalytic mechanism were very similar to those established in the prokaryotic models (21). However, questions about the processing of chemical-DNA adducts remain.…”
mentioning
confidence: 99%